2007
DOI: 10.1159/000112506
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Sublingual Immunotherapy for Japanese Cedar Pollinosis

Abstract: Background: Japanese cedar pollen represents an important and unique allergen. Sublingual immunotherapy (SLIT) has been suggested to be a highly effective route of desensitization against a variety of allergens. However, little information is available about its use in cedar pollen allergy. Methods: A blinded randomized, placebo-controlled trial employing SLIT for cedar pollinosis was conducted over a period of 6 months. Sixty-seven subjects were enrolled and the symptom scores during the pollen season were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 60 publications
2
34
1
Order By: Relevance
“…The trial was performed from October 2006 to June 2007. The treatment protocol consisted of graded courses of the extract in 50% glycerol, followed by maintenance therapy [4]. The extract was graded in 3 strengths: 20, 200 and 2,000 Japanese Allergy Units (JAU)/ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The trial was performed from October 2006 to June 2007. The treatment protocol consisted of graded courses of the extract in 50% glycerol, followed by maintenance therapy [4]. The extract was graded in 3 strengths: 20, 200 and 2,000 Japanese Allergy Units (JAU)/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of purified Cry j 1 was determined by the Lowry method using a detergent-compatible protein assay reagent (BioRad Laboratories Inc., Hercules, Calif., USA). CS712, which is a recombinant protein with 7 conjugated regions of T cell epitopes from Cry j 1 and Cry j 2 [4,5], was kindly provided by Daiichi Sankyo Co. Ltd. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SLIT increases serum levels of antigen-specific IgG4 and also increases the antigen-specific IgG4/IgE ratio [19,20], and it has been suggested that serum IgG acts as blocking antibody and is associated with symptomatic improvement [21]. In Japan, it was reported that allergen-specific SLIT increases serum Cry j 1-specific IgG4 antibody in patients with JC pollinosis [22].…”
Section: Igg4/iggmentioning
confidence: 99%